Physico-Chemical and Sensory Quality of Extruded Foods Developed from Rice and Defatted Soyflour /Chickpea Splits Supplemented with Dried Beetroot - D, MRIDULA; JAIN, DILIP; SINGH, K K; PATIL, R T; GUPTA, M K (Journal of Agricultural Engineering, 2012)
Extrudates were prepared from rice, defatted soya flour (DSF) or dehulled chickpea splits and dried beetroot using a twin-screw extruder and their physico-chemical properties were determined. Expansion ratio ranged from 3.207 to 2.833 and 3.244 to 3.029, while bulk density ranged from 192 to 260 and 162 to 240 kg.m-3, respectively. In both the cases, L* values decreased but a* values increased with increasing level of dried beetroot in the feed material. Protein, fat, ash content, crude fibre, carbohydrates and calories in both types of extrudates varied from 9.48 to13.05%, 0.57 to1.08%, 0.83 to1.73%, 0.79 to1.47%, 76.53 to 81.45%, and 364.37 to 373.06 kcal/100g, respectively. Supplementation levels of dried beetroot (up to 6% by mass) had significant effect on sensory characteristics of extrudates and indicated commercial scope with tailored healthful properties.